Optimization of citrus suhuiensis suspension culture conditions using Response Surface Methodology (RSM) - M. Fathil, Nur Alia; Mohamad Puad, Noor Illi; Azmi, Azlin Suhaida; Amid, Azura (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Friable callus of Citrus suhuiensis (C. suhuiensis) derived from its cotyledon seed was inoculated for cell suspension culture establishment. Face Centred Central Composite Design (FCCCD) and Response Surface Methodology (RSM) in Design Expert 9.0 software were used to optimize C. suhuiensis cell suspension culture conditions. Prior to that, one-factor-at-a-time (OFAT) method was carried out to determine the suitable ranges of three factors for FCCCD which are carbon source, plant growth regulators (PGRs) and inoculum size. The cells were cultivated in Murashige and Skoog (MS) media supplemented with different concentrations of sucrose (40-60 g/L), 0.25-0.75 mg/L 2,4-dichlorophenoxyacetic acid (2,4-D) and 5-15% (v/v) inoculum. Result showed that the maximum cell dry weight was 21.42 g/L when media containing sucrose at 50 g/L, 2,4-D at 0.5 mg/L and 15% of inoculum were used. Based on ANOVA analysis, the model was significant while the p-value showed that the linear terms of 2,4-D and inoculum size as well as the quadratic terms of glucose and 2,4-D were highly significant (p<0.01). Linear and quadratic effects of 2,4-D were significant, indicating that small changes of 2,4-D would alter C. suhuiensis cell density.